Intestinal Inflammation and the Gut Microflora - Derek M McKay (Canadian Journal of Gastroenterology)
The idea that the enteric microflora play a role in the pathogenesis or pathophysiology of inflammatory bowel disease (IBD) is not new. Indeed, identification of an infective cause for chronic IBD, and particularly for Crohn’s disease, has been the focus of extensive research efforts. During the 1990s, there has been a noticeable re-emergence of interest in the link between bacteria and functional bowel disorders, and the value of antibiotic therapy to treat gut inflammatory disorders. A variety of experimental evidence from both laboratory model systems and clinical investigations is reviewed with respect to a pivotal role for enteric bacteria in gut inflammation. The voluminous scientific literature on this subject precludes any comprehensive synopsis of the area; instead, pertinent studies are cited to illustrate the ability of bacteria and their products to evoke or exacerbate gut inflammation.